Operational guidelines for enhancing irrigation system efficiency in tubewell command - CHAUDHARI, S. S.; SUDHISHRI, S.; KHANNA, M.; DASS, ANCHAL; ROSIN, K. G.; V.A., BLESSY; SINGH, P. (Journal of Soil and Water Conservation, 2020)
In the light of increasing water scarcity and climate changes, there is the need to enhance the water productivity in irrigated agriculture. In India, the average irrigation project efficiency (Ep) is around 30%, especially in irrigated commands where surface irrigation method is prevalent. Therefore, the current study was under taken at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi farm (Mid-block, MB) with sandy loam to clay loam soil texture during 2016-17 with the objective of evaluation of surface irrigation hydraulics and water productivity parameters for major Rabi crops (wheat, mustard and chickpea). Irrigation efficiencies viz., conveyance (Ec), application (Ea), storage (Es), distribution (Ed) and project efficiency (Ep) varied from 60-70, 39-70, 70-90, 80-90% and 30- 45%, respectively. Water productivity for late and timely sown mustard was 0.69 kg/m3 and 0.74 kg/m3 (MB-3A-1 and 2), whereas 1.22, 1.14 kg/m3 for wheat in sandy loam and sandy clay loam, 0.77 and 1.16 kg/m3, respectively for chickpea and wheat in clay loam soils. To increase the conveyance efficiency up to 80% and also application efficiency, different combinations of dimensions for trapezoidal and rectangular best hydraulic sections were designed and cutoff times were given after simulating WinSRFR model. The irrigation performance indices given in this work can provide the measure to achieve more efficient irrigation management system